Melatonin prevents oxidative kidney damage in a rat model of thermal injury - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
Animal models of thermal trauma implicate oxygen radicals as causative agents in local wound response and distant organ injury following burn. This study was designed to determine the effect of melatonin treatment on levels of glutathione (GSH), malondialdehyde (MDA), protein oxidation (PO) and myeloperoxidase (MPO) activity in the kidney tissues of rats with thermal injury. Under ether anaesthesia, shaved dorsum of the rats was exposed to 90 degreesC bath for 10 s to induce burn injury. Rats were decapitated either 3 h or 24 h after burn injury. Melatonin was administered i.p. immediately after burn injury. In the 24-h burn group melatonin injections were repeated for two more occasions. In the sham group the same protocol was applied except that the dorsum was dipped in a 25 degreesC water bath for 10 s. Severe skin scald injury (30% of total body surface area) caused a significant decrease in GSH level, and significant increases in MDA and PO levels, and MPO activity at post-burn 3 and 24 hours. Treatment of rats with melatonin (10 mg/kg) significantly elevated the reduced GSH levels while it decreased MDA and PO levels as well as MPO activity. (C) 2002 Elsevier Science Inc. All rights reserved.
Keywords: burn; kidney; melatonin; lipid peroxidation; glutathione; myeloperoxidase; protein oxidation; TISSUE LIPID-PEROXIDATION; FREE-RADICALS; INFLAMMATION; GLUTATHIONE; MECHANISMS